Evaluation of Nurses’ Practices in Intensive Care Units Following Coronary Artery Bypass Grafting Patients in Baghdad City - Hu`sam A. Dawood (Iraqi National Journal of Nursing Specialties, 2023)
Objective: To evaluate nurses’ practices toward coronary artery bypass grafting (CABG) patients in the intensive care units (ICU) and to find out the relationship with some vanables. Methodology: A purposive sample of (50) staff nurses was selected out of three hospitals for cardiac surgery. The study instmment consisted of two major sections was constructed. It is based on the review of literature. First it is concerned with demographic data for nurses; and the second section is observationaL tool (checklist) is composed of six parts in which there mere (78) items. Reliability and validity of the observational checklist were determined through the analysis of a pilot study. Data were collected through the use of the observational tool and analyzed through the use of two statistical approaches; descriptive statistical analysis (frequencies, percentage, Standards Deviation, Range of scores, mean of scores and relative sufficiency; and inferential statistical analysis (correlation coefficient and chi-square test). Results: The findings of the study reveal that most of the nurses’ practices has poor scores, in intensive care units toward coronary artery bypass grafting patients, and it was found that, there is a significant relationship between level of education and nurse’s practices but no significant relationship between nurses’ practices and demographic variables which include age, gender, years of experience in nursing, years of experience in ICU and . training session. Recommendations: Based on the results of the study, the researcher recommends that developing assessment sheet for skill and daily note in the ICU, the education level should be improved, special training programs should be given for the nurses working in ICU and give patients and family education post operation. Nurses’ skills should be promoted to reduce or prevent complication post CABG.